Dunia Akademik Sebagai Sekte: Pengetahuan, Kekuasaan, dan Kekerasan dalam The Secret History oleh Donna Tartt - Noor, Aisha Zahrany Putri; Budiman, Manneke (Retorik: Jurnal Ilmu Humaniora, 2025)
Amongst the themes that literary works in the genre of dark academia foreground are power and abuse. In The Secret History (1992) by Donna Tartt, a book that is considered to be foundational for the dark academia genre, power dynamics plays a central role. Set in a small liberal arts college in rural Vermont, the book follows an exclusive, closed group of six classics students alongside their charismatic professor as they deal with the aftermath of the murder of one of their friends and the events leading up to it. This research aims to explore how the relationships amongst the characters and knowledge, power, and abuse affect their dynamics in Donna Tartt’s novel. Through textual analysis that applies Michel Foucault’s theory of power/knowledge and Robert Jay Lifton’s thought reform theory, this study reveals how knowledge can become a tool of power to control students into blind submission, like cult members, even in an academic environment where critical thinking is encouraged. This research offers an insight on how Tartt’s portrayal serves as a commentary on the danger of unchecked power and conformity within academic institutions.